Antifungal effect of selected European herbs against Candida albicans and emerging pathogenic non-albicans Candida species - Nacsa-Farkas, Elvira (Acta Biologica Szegediensis, 2014)
The anti-candidal effect of some European medicinal plants Allium ursinum (wild garlic or ramson); Aristolochia clematitis (birthwort), Melilotus officinalis (sweet clover), Salvia officinalis (garden sage) and Viscum album (mistletoe) was investigated. In general, C. incon-spicua, C. zeylanoides and C. norvegica were among the most sensitive species, while C. albicans together with C. orthopsilosis showed much lower sensitivity. Best results were achieved with wild garlic showing a broad spectrum anti-yeast activity in some cases with fungicidal MIC (3.52 mg/ml). The other plant extracts showed moderate, mainly fungistatic action.